Analisis Kepuasan Tenaga Kesehatan pada Penggunaan E-Puskesmas dengan Metode End User Computing Satisfaction (EUCS) di Puskesmas Klangenan - Maelivia Azilyah; Fitria Dewi Rahmawati; Yanto Haryanto; Bhakti Aryani (Lembaga Pengembangan Kinerja Dosen, 2026)
The implementation of digital health information systems, such as e-Puskesmas, plays an important role in supporting electronic medical records in primary healthcare facilities. However, technical constraints, including network instability and system integration issues, may affect user satisfaction among healthcare workers. This study aims to analyze healthcare workers’ satisfaction in using e-Puskesmas based on the End User Computing Satisfaction (EUCS) method. This research employed a quantitative analytic approach with a cross-sectional design, involving 35 healthcare workers at Puskesmas Klangenan using total sampling. The variables consisted of five EUCS dimensions, namely content, accuracy, format, ease of use, and timeliness. Data were collected using a structured questionnaire with a Likert scale and analyzed using descriptive statistics and Spearman correlation test. The results showed that user satisfaction was categorized as very satisfied across all EUCS dimensions, with mean scores ranging from 4.11 to 4.47. All EUCS dimensions had a positive and significant relationship with user satisfaction (p < 0.05), with format and ease of use showing the strongest correlations. It can be concluded that the quality of system and information in e-Puskesmas significantly influences healthcare workers’ satisfaction, indicating the need for continuous system development to support optimal healthcare services.